Making India great again : learning from our history - Rajivlochan, Meeta; Rajivlochan (London : Routledge, 2021)
How can India become a great country once again, is the question explored in this book. In the past, India had significant achievements in science, technology, mathematics and business. A failure to build robust institutional networks of information and trust and indifference of the state to business communities, brought all that crashing down within a generation. Many of these historical patterns persist till today. The ability to create wealth has everything to do with such networks. There was never any shortage of innovation in India. What was lacking was the ability to learn from their own experience. The building of learning networks and a learning ecosystem that could be used by people to leverage success - this is what is needed to unlock the huge talent pool that India possesses. This book addresses young, educated and aspiring Indians in different walks of life who are interested in contemporary issues relating to nation, society and economy. It puts forward some solutions to the problems that India faces. It would be of interest to anyone who would like to know how history can teach us to re-write the Indian growth story and to re-build a great nation. The book could also be used as reading material for students of history, political science, public administration, business administration, in under-graduate and post-graduate classes.Please note: This title is co-published with Manohar Publishers, New Delhi. Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka
OCLC-licensed vendor bibliographic record.
Keywords: India -- Economic conditions; India -- Social conditions; India -- History -- 1947-; POLITICAL SCIENCE / Public Policy / General